A digital reconstruction of the sunken "Villa con ingresso a protiro" in the underwater archaeological site of Baiae - Davidde Petriaggi, Barbara; Petriaggi, Roberto; Bruno, Fabio; Lagudi, Antonio; Peluso, Raffaele; Passaro, Salvatore (My University, 2018)
The Underwater Cultural Heritage represents a key aspect of our historical memory still little known due to a number of limitations imposed by the underwater environment. The aim of this paper is to explore the use of digital three-dimensional reconstructions to support the research about this immeasurable archaeological and historical resource. The whole virtual reconstruction process is described step by step, focusing on the iterative feedback allowing for reaching the best virtual reconstruction solutions, helping the archaeologists to better focus their reasoning through a detailed visual representation, and the technical experts to avoid misleading details in the final virtual reconstruction.